Modern land law - Thompson, Mark P. (Oxford University Press, 2009)
Taking a fresh, analytical approach, Mark P. Thompson introduces students to the basic principles of modern land law. Explaining and exploring all the key features of the subject, this concise and engaging text offers comprehensive and accessible coverage of all the major topics studied by undergraduates, addressing contemporary debates, and analysing the social context of modern land law, and the policy tensions to which it gives rise. This new edition has been fully revised and updated to take into account recent changes in land legislation. It contains extensive reference to the Land Registration Act 2002, discussion of the Electronic Communications Act 2000, Commonhold, and changes to mortgages as a result of the House of Lords decision in Royal Bank of Scotland (No.2) v Etridge. It also contains reduced coverage of the 1925 legislation. Designed to map directly on to mainstream university courses, this book remains the ideal text for undergraduates, retaining a traditional structure that reflects the way courses are taught, and avoiding excessive detail and the treatment of more esoteric topics.